Estimation of the indirect radiative effects of aerosol on climate using a general circulation model - West, REL (2012)
The indirect effects of anthropogenic aerosols—through their interactions with clouds—are currently one of the most uncertain perturbations to the radiative energy balance at the top of the atmosphere. A crucial link between aerosol and cloud is that aerosols can act as cloud condensation nuclei (CCN). This microphysical process must be parameterised if the large-scale effects are to be represented in a general circulation model (GCM). Theoretical work presented in this thesis highlights the importance of incorporating the kinetic limitations on droplet formation in aerosol activation parameterisations. HadGEM-UKCA is a GCM, capable of representing the chemical and microphysical aerosol processes required to model CCN accurately. The author has incorporated a Köhler theory based parameterisation of aerosol activation into HadGEM-UKCA, to facilitate quantitative predictions of the indirect aerosol effects. This thesis presents an estimate of the range of uncertainty in such predictions attributable to the choice of parameterisation of the sub-grid-scale variability of vertical velocity. Results of simulations demonstrate that the use of a characteristic updraught velocity cannot replicate results derived with a distribution of vertical velocities, and is to be discouraged in GCMs. Consequently, work focuses on the effect of the variance (<var>σ</var>w2) of a Gaussian pdf of vertical velocity. Fixed values of <var>σ</var>w and a configuration in which <var>σ</var>w depends on turbulent kinetic energy are tested. Results from the mid-range fixed <var>σ</var>w and TKE-based configurations both compare well with vertical velocity distributions and cloud droplet number concentrations measured in situ. However, the sparse set of available measurements does not provide enough of a constraint to recommend one or the other as the best configuration globally. The radiative flux perturbation (RFP) due to the total effects of anthropogenic aerosol is estimated at −1.7Wm−2 for the TKE-based configuration. To the extent that it is valid to decouple the individual aerosol effects, the direct effect accounts for approximately −0.6Wm−2 of the total, the cloud albedo effect −0.8Wm−2 and the cloud lifetime effect −0.3Wm−2, indicating that these effects are additive within HadGEM-UKCA. Total aerosol RFP ranges from −1.4Wm−2 from simulations with <var>σ</var>w=0.1ms−1, up to −2.0Wm−2 for <var>σ</var>w=0.7ms−1. This range of 0.6Wm−2 corresponds to almost a third of the total estimate of −1.9Wm−2, obtained with the mid-range value of <var>σ</var>w=0.4ms−1. Reducing the uncertainty in the parameterisation of <var>σ</var>w is therefore an important step towards reducing the uncertainty in estimates of the indirect aerosol effects.